Flexible surface acoustic wave devices and its applications in microfluidics. Issue 1659 (9th January 2014) - Zhou, Jian; He, Xingli; Wang, Wenbo; Hu, Nana; Jin, Hao; Xu, Y.; Dong, Shurong; Wang, Demiao; Fu, Y.Q.; Luo, J. K.
Abstract: Flexible electronics and microsystems are an emerging technology with a tremedous impact to the future electronics and information technology and widespread applications. Various devices and microsystems have been developed. Surface acoustic wave (SAW) devices are a type of essential device for electronics, microsensors and microsystems; however there is no activity on the development of flexible SAW devices yet. This paper reports the development of flexible SAW devices on cheap, bendable and disposable plastic films. Flexible SAW devices with resonant frequency of 198.1 MHz and 447 MHz for the Rayleigh and Lamb waves respectively have been obtained with a large transmission signal up to 18dB. The flexible SAW devices have also demonstrated their ability for acoustic streaming with a velocity up to 3.4 cm/s and for particle concentration. The results have clearly demonstrated that the flexible SAW devices have great potential for applications in electronics and microsystems.